Multifaceted roles of IKZF1 gene, perspectives from bench to bedside - Feng, Lin; Zhang, Hang; Liu, Ting (Frontiers in Oncology, 2024)
The IKZF1 gene encodes a transcription factor that belongs to the family of zinc-finger DNA-binding proteins associated with chromatin remodeling. The protein product, IKAROS, had been proved to regulate lymphopoiesis.Subsequent mouse model studies have further confirmed its regulating role in lymphopoiesis as well as in hematopoiesis; besides, it associates with immune function, certain immune disorders like common variable immunodeficiency and dysgammaglobulinemia have been proved to be associated with germline IKZF1 mutations. Dysfunction of IKAROS also bears paramount significance in leukemic transformation and alterations of IKZF1 gene predicts a poor prognosis in hematological malignancies. As an independent prognostic marker, IKZF1 has been incorporated in the risk stratification of BCP-ALL and stratification-guided therapy has also been generated. In this review, we provide a concise and comprehensive overview on the multifaceted roles of IKZF1 gene.